Breaking Boundaries Challenges and Opportunities for Internationalizing MSMEs in Solo to Achieve SDG 1 and 8 - Satria, Randhi; Tiara Scoorpy Ananda Putra, Nyphadear; Darmawan, Arif; Setyaka, Virtuous (Global Political Studies Journal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are vital for achieving SDG 1 (poverty alleviation) and SDG 8 (inclusive and sustainable economic growth). In Surakarta (Solo), MSMEs significantly contribute to local employment and poverty reduction. However, many face challenges in expanding beyond the local market, particularly in accessing foreign markets. This study analyses the role of Solo’s MSMEs in advancing SDGs 1 and 8 and explores barriers to global market entry. Using a qualitative approach through literature review and secondary data from the Surakarta Bureau of Statistics (BPS), the research identifies key obstacles and opportunities for MSMEs in supporting poverty reduction and economic growth. The Pentahelix Model—government, academia, business, civil society, and media—is applied to highlight the collaborative framework needed for MSMEs’ internationalization. Strengthening these stakeholders’ synergy can create an enabling environment, improving access to finance, training, and market information. A comprehensive strategy involving policy support, capacity building, and resource facilitation is essential to enhance MSMEs’ competitiveness in global markets, thereby maximizing their contribution to Sustainable Development Goals 1 and 8.  Keywords— MSMEs (Micro, Small, and Medium Enterprises), Sustainable Development Goals (SDGs), Poverty Eradication, Inclusive Economic Growth, International Market Access